SP9.1.4 Performance and Cost-Effectiveness of a Virtual Consultation Clinic for 2-Week-Wait Colorectal Cancer Referrals – A Response to the Covid-19 Pandemic. (9th August 2022) - Davidson, Christopher; Conlon, Sinead; Al-Fagih, Othman; Khan, Nauwab; Cheetham, Drostan; Patel, Vanash
Abstract: Aims: Measure performance and cost effectiveness of a Virtual Consultation (VC) clinic, compared to face-to-face (FF) clinic, for 2-week-wait (2WW) colorectal cancer (CRC) referrals, which did not meet the criteria for nurse-led Telephone Assessment Service. Methods: 2WW CRC referrals were triaged by a colorectal surgeon to either a doctor-led VC or FF clinic. Demographics, referral indications, and primary outcome measures (time to clinic/results; investigation type; cancer detection rate) were compared pre-pandemic (November 2019–January 2020) and during the pandemic (May–June 2021). Results: 158 (pre-pandemic) and 160 (pandemic) consecutive patients were analysed, with no difference in age (74 vs. 75 years, p=0.936). During the pandemic, patients were referred with an increased number of positive FIT tests (29 vs. 13%, p<0.001), were more likely to have computerised tomography (65 vs. 45%, p=0.003), had a longer time from referral to clinic assessment (10 vs. 8 days, p=0.002), but were informed of results more promptly (59 vs. 138 days, p<0.001) than pre-pandemic patients. During the pandemic patients were assessed earlier via VC than FF clinics (9 vs. 11 days, p=0.049). There were no significant differences in cancer detection rate pre or during the pandemic (12 vs. 8%, p=0.187), or between VC and FF clinic during the pandemic (6 vs. 12%, p=0.294). Cost effective analysis showed £15, 000 per annum saving with doctor-led VC clinic. Conclusion: Virtual consultation for 2WW CRC referrals may improve efficiency without compromising the cancer detection rate, as well as reducing risk of Covid-19 transmission and being more cost effective.